Role of Selling-Out as a Mediation Variable of Retail Store Trust on Selling-In in Pulung Food Products - Dwi Rahayu; Alimudin Rizal Riva’i (Budapest International Research and Critics University, 2022)
This study aims to determine the role of selling-out as a mediating variable of retail store trust in selling-in in Pulung Food products. This research is quantitative. The type of research used is case study research. A case study is a research strategy, an empirical study that investigates a phenomenon in a real-life setting. The purpose of the research is to obtain the necessary data. The sample used was 45 respondents who were retail store owners who partnered with UD Pulung Food. The analytical method used is Partial Least Square (PLS) with the help of the SmartPLS 3.0 application. Based on the results of the study, it is known that the significance value for the influence of trust on the Ling - in the cell, the original sample value of 0.4 7 7 is positive and the t count is 4.576 > t-table (1.960) and the p-value is 0.000 <0.05 and the original sample is positive. Thus the Hypothesis in this study is accepted. That is, there is a positive and significant influence on trust in trading. To build the intensity of cooperation that can achieve results, it is not only based on the interests of both parties but needs to be based on trust (mutual trust), namely a business relationship, which in business transactions occurs when there is trust between the two parties.